Needs assessment for faculty development in health professions education at a medical university in Karachi, Pakistan - Tabassum Zehra; Sana Saeed; Rahila Ali; Amber Sultan; Hussain, Areeba (Journal of the Pakistan Medical Association, 2022)
Faculty Development (FD) embraces all educational activities used by teachers to improve their knowledge and skills for enhancing their academic competencies. This study aimed to identify the areas in Health Professions Education (HPE) in which formal faculty development is required. A needs assessment survey was conducted from among the faculty members at the Aga Khan University (AKU), Karachi, Pakistan, and the French Medical Institute for Mother and Children, Afghanistan. Data was analysed using SPSS 20.0 and reported frequencies and percentages according to various academic tracks. Competency-based curricula (51%), providing effective feedback (51%), developing Objective Structured Clinical Exam (51%), and clinical supervision (48%) were identified as significant areas for faculty development. Faculty in clinician teacher and clinician educator track require advanced training, i.e., Masters and PhD in HPE. The needs assessment facilitated prioritising the areas for FD. This will contribute to enhancing academic practices and inculcating the culture of lifelong learning.